2010
DOI: 10.1007/s10815-010-9385-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the safety of time-lapse observations for human embryos

Abstract: Purpose To assess the effects of light from an integrated optical microscope and evaluate the safety of time-lapse observations using a built-in microscope incubator. Methods We prospectively compared the fertilization rate and embryonic morphology after intracytoplasmic sperm injection between embryos cultured with time-lapse observations every 15 min in an incubator with an integrated optical microscope and embryos with intermittent observations (once a day) in conventional incubators. Results No significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(56 citation statements)
references
References 21 publications
3
52
0
1
Order By: Relevance
“…They also found a signiicant higher miscarriage rate in the TLS group [13]. These results are in line with other studies, which showed similar results in good quality embryos, embryo development, blastocyst rate, implantation, and ongoing pregnancy rates between customary culture and TLS [14][15][16]. In the same way, in a two-part study, poor-prognosis patients have shown no diferences in Day-3 embryo quality, implantation, and clinical pregnancy rates between embryos cultured in EmbryoScope™ and conventional culture, whereas in the second portion, embryos developed in the EmbryoScope™ revealed signiicantly poorer quality on Day 3 compared to standard-cultured embryos [17].…”
Section: Arguments Against Predictive Value Of Tlssupporting
confidence: 88%
“…They also found a signiicant higher miscarriage rate in the TLS group [13]. These results are in line with other studies, which showed similar results in good quality embryos, embryo development, blastocyst rate, implantation, and ongoing pregnancy rates between customary culture and TLS [14][15][16]. In the same way, in a two-part study, poor-prognosis patients have shown no diferences in Day-3 embryo quality, implantation, and clinical pregnancy rates between embryos cultured in EmbryoScope™ and conventional culture, whereas in the second portion, embryos developed in the EmbryoScope™ revealed signiicantly poorer quality on Day 3 compared to standard-cultured embryos [17].…”
Section: Arguments Against Predictive Value Of Tlssupporting
confidence: 88%
“…Nor did we find any differences in clinical pregnancy rate or implantation rate. Though several studies have reported similar development in time-lapse incubators compared to conventional incubators, none of these have been conducted as randomized clinical trials (RCT) [18,24,26,41]. Most reports have been supplementary observations in descriptive studies investigating different aspects of development.…”
Section: Discussionmentioning
confidence: 99%
“…Before introducing timelapse monitoring in a clinical setting, the safety of the instrument must therefore be properly documented. Comparisons have been made between embryos, both mouse and human, cultured in conventional incubators and time-lapse instruments, without reports of any adverse effects on development or implantation rate [5,15,18,24,26,32,41]. However, none of the previous studies were conducted as randomized clinical trials and the included human embryos derived from oocyte donor cycles [5] may not be representative of embryos from infertile couples.…”
Section: Introductionmentioning
confidence: 99%
“…With the rapidly spreading use of time-lapse observations, especially on human embryos in fertility clinics, it is important to investigate, whether light exposure for image recording affects or even compromises the embryo's developmental competence. Different measures based on studies of animal model embryos have already been implemented to minimize light exposure of visible [15] or longer wavelength light [2,15,16], and in combination with sensitive camera systems it is possible to obtain high quality images for evaluation without disadvantages on embryonic development and quality [17]. Microscopy typically works with visible light (380-700 nm), where wavelengths <500-550 nm are regarded as harmful to the development and quality of mammalian embryos [2,15].…”
Section: Introductionmentioning
confidence: 99%